Pengaruh Kemudahan, Kemanfaatan Dan Risiko Terhadap Minat Penggunaan Financial Technology Pada Pembayaran Digital Pariwisata Di Kabupaten Sumenep - Purnama Ardian; R Gatot Heru Pranjoto; Samsuki Samsuki (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the influence of convenience, usefulness and risk on interest in financial technology in using digital payments. The method used in this research is to use a quantitative method by collecting primary data, distributing questionnaires to tourism parties using the random sampling method IBM SPSS Ver. 25 statistical analysis software was used to process the data findings. Multiple linear regression analysis was used to test the research data and factors. The hypothesis of this research is: there is a positive and significant influence of convenience and usefulness on financial technology's interest in using digital payments and there is a negative influence of risk on financial technology's interest in using digital payments. The findings in this research are: 1. The convenience variable has a significant positive effect on financial technology interest in using digital payments. 2. The usability variable has a significant positive effect on financial technology interest in using digital payments. 3. Risk variables have a negative effect on financial technology's interest in digital payments Keywords: Financial Technology, Convenience, Benefits, Risks, Interest In Digital Payments, Quantitative